PEMAAFAN HAKIM (RECHTERLIJK PARDON) DALAM KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) BARU DI SISTEM PEMIDANAAN INDONESIA - Anza Ronaza Bangun (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
Judicial Pardon (Rechterlijke Pardon) refers to the authority granted to judges to forgive a person who is guilty of committing a minor criminal offense before a verdict is rendered. This research aims to explore in greater depth the regulatory system of Judicial Pardon (Rechterlijk Pardon) in Indonesia’s Criminal Code (KUHP), compare it with similar provisions in other countries, examine the urgency of incorporating Judicial Pardon (Rechterlijk Pardon) into the new Criminal Code (KUHP), and identify the types of criminal offenses that may be resolved through Judicial Pardon. The method used in this study is a normative juridical research method with a descriptive-analytical character. Theories employed include the theory of comparative law, the theory of judicial pardon, and the theory of law enforcement. The research uses secondary data, which includes primary legal materials, secondary legal materials, and tertiary legal materials. The techniques and tools for data collection include library research, involving the study of various literature sources such as books, legislation, and course materials related to law, as well as documentary research. The data in this research is analyzed using qualitative data analysis methods. The findings of the study reveal thatJudicial Pardon (Rechterlijk Pardon)has been included in Article 54 paragraph (2) of Law Number 1 of 2023 concerning the National Criminal Code (KUHP). The regulation of Judicial Pardon (Rechterlijk Pardon) in Indonesia, compared to that in several European countries such as Greece, Portugal, and the Netherlands, demonstrates that each country’s legal framework has its own strengths and weaknesses regarding the concept and implementation of Judicial Pardon (Rechterlijk Pardon).